Lamé Functions - 29.3 Definitions and Basic Properties

From testwiki
Revision as of 12:09, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
29.3#Ex3 α p = 1 2 ( ν - 2 p - 2 ) ( ν + 2 p + 3 ) k 2 subscript 𝛼 𝑝 1 2 𝜈 2 𝑝 2 𝜈 2 𝑝 3 superscript 𝑘 2 {\displaystyle{\displaystyle\alpha_{p}=\tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}}}
\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}

alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2)
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex4 γ p = 1 2 ( ν - 2 p + 1 ) ( ν + 2 p ) k 2 subscript 𝛾 𝑝 1 2 𝜈 2 𝑝 1 𝜈 2 𝑝 superscript 𝑘 2 {\displaystyle{\displaystyle\gamma_{p}=\tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}}}
\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}

((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2)
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex5 α p = 1 2 ( ν - 2 p - 2 ) ( ν + 2 p + 3 ) k 2 subscript 𝛼 𝑝 1 2 𝜈 2 𝑝 2 𝜈 2 𝑝 3 superscript 𝑘 2 {\displaystyle{\displaystyle\alpha_{p}=\tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}}}
\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}

alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2)
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex6 γ p = 1 2 ( ν - 2 p + 1 ) ( ν + 2 p ) k 2 subscript 𝛾 𝑝 1 2 𝜈 2 𝑝 1 𝜈 2 𝑝 superscript 𝑘 2 {\displaystyle{\displaystyle\gamma_{p}=\tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}}}
\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}

((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2)
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex7 α p = 1 2 ( ν - 2 p - 3 ) ( ν + 2 p + 4 ) k 2 subscript 𝛼 𝑝 1 2 𝜈 2 𝑝 3 𝜈 2 𝑝 4 superscript 𝑘 2 {\displaystyle{\displaystyle\alpha_{p}=\tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2}}}
\alpha_{p} = \tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2}

alpha[p] = (1)/(2)*(nu - 2*p - 3)*(nu + 2*p + 4)*(k)^(2)
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 3)*(\[Nu]+ 2*p + 4)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex8 β p = ( 2 p + 2 ) 2 ( 2 - k 2 ) subscript 𝛽 𝑝 superscript 2 𝑝 2 2 2 superscript 𝑘 2 {\displaystyle{\displaystyle\beta_{p}=(2p+2)^{2}(2-k^{2})}}
\beta_{p} = (2p+2)^{2}(2-k^{2})

beta[p] = (2*p + 2)^(2)*(2 - (k)^(2))
Subscript[\[Beta], p] == (2*p + 2)^(2)*(2 - (k)^(2))
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex9 γ p = 1 2 ( ν - 2 p ) ( ν + 2 p + 1 ) k 2 subscript 𝛾 𝑝 1 2 𝜈 2 𝑝 𝜈 2 𝑝 1 superscript 𝑘 2 {\displaystyle{\displaystyle\gamma_{p}=\tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2}}}
\gamma_{p} = \tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2}

((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p)*(nu + 2*p + 1)*(k)^(2)
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p)*(\[Nu]+ 2*p + 1)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -